Kompetensi adab pada siswa Sekolah Menengah Pertama An-Nahl Islamic School - Frinaety, Tuty Any (Tawazun: Jurnal Pendidikan Islam, 2023)
Education is a fundamental pillar in producing quality generations. The deterioration of generations is largely attributed to the decline in moral and ethical education. The emergence of various issues related to adolescent delinquency has garnered attention, with families and schools being heavily implicated. Currently, the role of the family has shifted from one of protection and instilling moral values to a formal institution that either fails to provide protection or becomes the root of problems, such as disharmony and frequent conflicts and violence by parents. Emphasizing knowledge of faith, belief, and moral conduct is crucial in educational institutions, as well as the exemplary behavior of parents. However, adab (moral conduct) learning in schools is inadequate, and the role models among educators are lacking, resulting in a significant deficiency in adab competence among students today. Therefore, prioritizing adab education is crucial, aiming to cultivate students' strong adab competence. One educational institution that prioritizes adab in its curriculum is An-Nahl Islamic School, a Junior High School that envisions and strives to shape Qur'anic-character leaders with a global perspective and concern for the environment. The objective of this research is to understand and describe the implementation of adab education and its competence among students at An-Nahl Islamic School. The research adopts a qualitative approach, specifically field research, employing methods such as interviews, observations, and relevant literature. The findings indicate that an education based on the curriculum of faith, the Quran, and adab, reinforced by integrated learning programs with Islamic values, leads to excellent adab competence, including diligence in worship, respect and obedience towards parents and teachers, and performing acts of kindness towards others and the environment. Abstrak Pendidikan memiliki peran sentral dalam menciptakan generasi yang berkualitas. Kelemahan pendidikan adab dan moral menjadi penyebab utama keruntuhan generasi. Masalah remaja, keluarga, dan sekolah terkait dengan perilaku negatif remaja semakin menjadi perhatian. Saat ini, peran keluarga telah berubah dari menjadi pelindung dan pengajaran nilai-nilai moral menjadi lembaga formal yang tidak memberikan perlindungan, bahkan menjadi sumber masalah seperti ketidakharmonisan, pertengkaran, dan kekerasan oleh orang tua. Penanaman ilmu aqidah, iman, dan adab di lembaga pendidikan serta keteladanan orang tua sangat penting. Pembelajaran adab di sekolah sangat minim, begitu juga dengan contoh teladan dari pendidik, sehingga kompetensi adab peserta didik saat ini sangat kurang. Oleh karena itu, pembelajaran adab harus menjadi prioritas utama dengan harapan peserta didik memiliki kompetensi adab yang baik. Salah satu lembaga pendidikan yang mengintegrasikan adab dalam kurikulumnya adalah Sekolah Menengah Pertama An-Nahl Islamic School, yang memiliki visi misi untuk membentuk pemimpin berkarakter Qur'ani, berwawasan global, dan peduli pada lingkungan. Tujuan penelitian ini adalah untuk mengetahui dan mendeskripsikan implementasi pendidikan adab serta kompetensi adab pada siswa Sekolah Menengah Pertama An-Nahl Islamic School. Penelitian ini menggunakan metode penelitian kualitatif dengan jenis penelitian lapangan, dan menggunakan metode wawancara, observasi, dan studi kepustakaan yang terkait. Hasil penelitian menunjukkan bahwa pendidikan yang berbasis pada kurikulum iman, Al-Quran, dan adab, yang diperkuat dengan program pembelajaran yang terintegrasi dengan nilai-nilai Islam, akan menghasilkan kompetensi adab yang baik, seperti kedisiplinan dalam beribadah, menghormati dan taat pada orang tua dan guru, serta berperilaku baik terhadap sesama dan lingkungan.